El Covid-19 y la Guerra Invisible: ¿Es el Fin de la Hospitalidad? / Covid and the Invisible War: Is this the End of Hospitality? - Korstanje, Maximiliano E (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2020)
RESUMEN El brote del virus conocido como Sars-Cov2 [o coronavirus] ha sido golpe significativo que afirma una tendencia iniciada luego de 2001 a la auto canibalización o fin de la hospitalidad occidental, sino que transforma el propio cuerpo y lo dispone como un arma para atacar al otro. Como ya se ha mencionado, la vieja dicotomía entre el turista deseado como un agente de crecimiento económico y el inmigrante temido como huésped no deseado, da paso a un nuevo paisaje, donde el turista es visto – con cierta sospecha – como un potencial enemigo. Como la guerra contra el cáncer en 1970, la guerra contra el crimen local en los 1990, y la guerra contra el terror en 2001, ahora el mundo vive la guerra contra un virus. En este nuevo mundo, la hospitalidad clásica cede hacia una hospitalidad absoluta donde el hotel se recicla como hospital. PALABRAS CLAVES Hospitalidad; Turismo; Coronavirus; Covid19; El fin del Turismo. ABSTRACT The recent virus outbreak resulted from Sars-Cov2 [coronavirus disease] not only has been a serious blow to the Western social imaginary, likely affirming a tendency ignited just after 2001 to the self-cannibalization – or at the best the end of hospitality as we know it –, but also disposed of the body as a potential killer who affects the public health. As this paper shows, the old dichotomy revolving around a desired tourist who is an agent of wealth production and globalization and the undesired migrant has been blurred. Now the global tourist is widely seen with some mistrust, as a potential enemy who may place the societal order in jeopardy. Like the war against Cancer in 1970s decade, the war against the local crime in the 1980, or the war on terror just after 9/11, now the world has declared the war against a virus. In this new world, the sacred law of hospitality is basically revisited according to the passage from an absolute to an unconditional hospitality [a-la Derrida]. KEYWORDS Hospitality; Tourism; Coronavirus Disease; Covid19; The End of Tourism. AUTORIA Maximiliano E Korstanje – Doctor. Profesor Universidad de Palermo, Buenos Aires, Argentina, e en la University of Leeds, Leed, Reino Unido. Currículo: https://www.igi-global.com/affiliate/maximiliano-korstanje/332098. E-mail: mkorst@palermo.edu REFERENCIAS Amoore, L., Marmura, S. & Salter, M. B. (2008). Smart borders and mobilities: Spaces, zones, enclosures. Surveillance & Society, 5(2), 96-101. <a href="https://scholar.google.com/scholar?hl=es&as_sdt=0%2C5&q=Amoore%2C+L.%2C+Marmura%2C+S.+%26+Salter%2C+M.+B.+%282008%29.+Smart+borders+and+mobilities%3A+Spaces%2C+zones%2C+enclosures.+Surveillance+%26+Society%2C+5%282%29.&btnG=">Link Altheide, D. (2018) Terrorism and the Politics of fear. New York, Rowman & Littlefield. Adey, P., Bissell, D., Hannam, K., Merriman, P. & Sheller, M. (Eds.). (2014). The Routledge handbook of mobilities. London: Routledge. Augé, M. (1996). El sentido de los otros: actualidad de la antropología. Madrid, Grupo Planeta (GBS). Augé, M. (1998). Viaje Imposible. Barcelona: Gedisa. Augé, M. (2007). El objeto de la antropología hoy. Psicoperspectivas, 6(1), 9-21. Link Bauman, Z. (2005). Liquid life. Cambridge: Polity Press. Bauman, Z. (2011). Collateral damage: Social inequalities in a global age. Cambridge: Polity Press. Bauman, Z. (2013). Liquid modernity. New York: John Wiley & Sons. Blaut, J. M. (1989). Colonialism and the rise of capitalism. Science & Society, 53(3), 260-296. Link Bryant, J. M. (2006). The West and the rest revisited: Debating capitalist origins, European colonialism, and the advent of modernity. Canadian Journal of Sociology, 31(4), 403-444. Link Burnham, M. (1999). Captivity & sentiment: cultural exchange in American literature, 1682-1861. London: Dartmouth College Press. Derrida, J., & Dufourmantelle, A. (2000). Of hospitality. Stanford: Stanford University Press. Harris, M. (2001). The rise of anthropological theory: A history of theories of culture. Chesnut Creek: AltaMira Press. Hart, J. (2003). Comparing Empires: European Colonialism from Portuguese Expansion to the Spanish-American War. New York: Springer. Kay, D. A. (1967). The politics of decolonization: The new nations and the United Nations political process. International Organization, 21(4), 786-811. Link Korstanje, M. (2012). Reconsidering cultural tourism: an anthropologist's perspective. Journal of Heritage Tourism, 7(2), 179-184. Link Korstanje M (2017). Terrorism, Tourism and the end of hospitality in the West. New York: Palgrave Macmillan. Korstanje M (2018a) The Mobilities Paradox: a critical analysis. Cheltenham: Edward Elgar. Korstanje, M. E. (2018b). The Challenges of democracy in the War on terror: the liberal state before the advance of terrorism. Routledge. Kundnani, A. (2014). The Muslims are coming! Islamophobia, extremism, and the domestic war on terror. London: Verso Trade. Lewis, D. (1973). Anthropology and colonialism. Current Anthropology, 14(5), 581-602. Link Lyon, D. (2001). Surveillance society: Monitoring everyday life. London: McGraw-Hill Education. Palmer, C. A. (1994). Tourism and colonialism: The experience of the Bahamas. Annals of tourism Research, 21(4), 792-811. Link Pels, P. (1997). The anthropology of colonialism: culture, history, and the emergence of western governmentality. Annual review of anthropology, 26(1), 163-183. Link Pratt, M. L. (2007). Imperial eyes: Travel writing and transculturation. New York: Routledge. Santana Talavera, A. (2003). Turismo cultural, culturas turísticas. Horizontes Antropológicos, 9(20), 31-57. Link Strong, P. T. (2018). Captive selves, captivating others: The politics and poetics of colonial American captivity narratives. Abingdon: Routledge. Virilio, P. (1995). Speed and information: Cyberspace alarm! CTheory, 8-27. LInk Virilio, P. (2005). Desert screen: War at the speed of light. London: A&C Black. Wolfe, P. (1999). Settler colonialism. London: A&C Black. PROCESSO EDITORIAL SEÇÃO ESPECIAL COVID-19 Recebido 11 JUN 2020; Aceito 14 JUN 2020.